Al-Akhá¹Äâ€™u al-á¹¢autiyah fÄ« QirÄâ€™ati al-Nuá¹£Å«si al-â€˜Arabiyyah bi IstikhdÄmi Taá¹bÄ«qÄti Praat - Nafisah, Nurzayyini; Sauri, Sofyan; Nurbayan, Yayan (Departemen Pendidikan Bahasa Arab, 2022)
This research was motivated by Arabic phonological errors that occurred in students during reading skills learning. Researchers consider it important to examine these problems. Therefore, through this study, the researcher will analyze what phonological errors occur among students. The research design used in this research is content analysis, while the language research method used is the listening method with the free-to-talk listening technique, note-taking technique, and recording technique. The results showed that there were many pronunciation errors in the letters hamzah and 'ain. Some of the factors that cause phonological errors include; First, the sound of the letter is a consonant sound that is difficult to pronounce, so the informant replaces it with a sound near the point of articulation. Second, is the lack of practice in pronouncing consonants such as communicating in Arabic, reading the Qur'an or Arabic discourse. The solution to overcome these phonological errors is the principle of repetition and habituation in learning. The trick is to present a reading in the form of a simple text. The contents contain the forms of phonological errors which have been described in the following discussion. This simple text is made as much as possible until the students' ability to pronounce the letters is good and correct.